2009
DOI: 10.1039/b813359j
|View full text |Cite
|
Sign up to set email alerts
|

Onset of carbon–carbon bonding in the Nb5Cy(y = 0–6) clusters: a threshold photo-ionisation and density functional theory study

Abstract: . Onset of carbon-carbon bonding in the Nb5Cy (y = 0-6) clusters : a threshold photo-ionisation and density functional theory study. Physical Chemistry Chemical Physics, 11(7), 1060-1068. We have used photo-ionisation efficiency spectroscopy to determine the ionisation potentials (IPs) of the niobium-carbide clusters, Nb 5 C y (y = 0-6). Of these clusters Nb 5 C 2 and Nb 5 C 3 exhibit the lowest IPs. Complementary density functional theory calculations have been performed to locate the lowest energy isomers fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(53 citation statements)
references
References 37 publications
9
41
1
Order By: Relevance
“…23 The vibrational temperature of the clusters is estimated to be ϳ300 K as the extracted IEs of Nb 3 C 2 and Nb 5 C 2 in our previous studies were found to be only slightly lower ͑Ͻ0.04 eV͒ than the adiabatic IEs determined via PFI-ZEKE photoelectron spectroscopy. 22,24,25 The IE values determined for all the Ta 3 ZrC y ͑y =0-4͒ clusters are displayed in the PIE spectra and are also tabulated later. For the Ta 3 ZrC y series, relative to the IE of Ta 3 Zr, addition of one C atom only reduces the IE very slightly ͑0.05 eV͒.…”
Section: B Pie Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The vibrational temperature of the clusters is estimated to be ϳ300 K as the extracted IEs of Nb 3 C 2 and Nb 5 C 2 in our previous studies were found to be only slightly lower ͑Ͻ0.04 eV͒ than the adiabatic IEs determined via PFI-ZEKE photoelectron spectroscopy. 22,24,25 The IE values determined for all the Ta 3 ZrC y ͑y =0-4͒ clusters are displayed in the PIE spectra and are also tabulated later. For the Ta 3 ZrC y series, relative to the IE of Ta 3 Zr, addition of one C atom only reduces the IE very slightly ͑0.05 eV͒.…”
Section: B Pie Experimentsmentioning
confidence: 99%
“…This value is estimated by the energy changes observed for the Nb x C y isomers ͑without carbon-carbon bonding͒ by extending the SDD basis set on the C atoms to an aug-cc-pVTZ basis set 24,25 and a separate study correlating the experimental properties of the most abundant Nb 9 isomer with DFT calculations. 28 DFT calculations have shown that Zr 4 has a slightly distorted tetrahedral geometry of high spin ͓ 7 AЈ , C s ͔, 29 whereas our calculations on Ta 4 give an ideal closed-shell tetrahedron…”
Section: Dft Calculated Isomersmentioning
confidence: 99%
“…Previous experience in our group, using the B3P86 functional, confirms the tendency of this functional to predict IPs that are 0.3-1.0 eV higher than experimentally measured values. [23][24][25] Using the smallest basis set combination at the MRCI and MRCI+ Q levels, the predicted IPs of 4.55 and 4.80 eV, respectively, are substantially below the experimental value. The addition of unlinked quadruple excitations increased the calculated IP value by 0.25 eV; however the resultant value is still Ϸ0.6 eV below the experimental value.…”
Section: Ip Calculationsmentioning
confidence: 99%
“…Upon supersonic expansion, the internal vibronic temperature of all clusters formed in the ablation process is ϳ300 K, as reported in our previous papers. 42,43 The neutral clusters formed in the laser ablation process are ionized with the frequency doubled output of a Nd:YAG pumped dye laser ͑220-280 nm͒ and extracted perpendicularly using deflection plates and an Einzel lens into the TOF-MS flight region and onto a double microchannel plate detector. The resulting cluster signal is then amplified ϫ25 with a commercial preamplifier ͑Stanford SR445͒ and delivered to a digital oscilloscope ͑LeCroy 9350 a.m., 500 MHz͒ for averaging ͑1000 laser shots͒ before being sent to a PC for analysis.…”
Section: A Experimental Methodsmentioning
confidence: 99%
“…[42][43][44] This is attributed to the nature of the B3P86 functional. Therefore, the IEs are corrected with respect to the RhHo 2 bare metal cluster as we are primarily concerned with how the IE changes with respect to the sequential addition of oxygen atoms.…”
Section: Comparison Between Experimental and Theoretical Datamentioning
confidence: 99%